Peculiarities of cytokine type of regulation of immune answer in women with ovarian endometriomas - O. S. Shapoval; L. L. Vorontsova (Zaporožskij Medicinskij Žurnal)
The problem of improving the treatment of endometrioid ovarian cysts is actual. The aim of the work was to reveal the features of the cytokine type of regulation of the immune response in women with ovarian endometriomas.